Estudo prospectivo de toxoplasmose em pacientes oncológicos em tratamento quimioterápico - Radin, Jaqueline (2011)
The Toxoplasma gondii is a protozoan which causes opportunistic infections in individuals with a compromised immune system. There exist a lot of studies correlating toxoplasmosis with immunosuppressed patients, however, in neoplasia carriers, who may suffer a process of immunosuppression during the chemotherapy, few studies were conducted. The aim of the present study was to evaluate, through serological profile, the risk of acute infection (or reactivation) of T.gondii in cancer patients who had chemotherapy treatment in the School Hospital of Pelotas Federal University and in the Radiotherapy and Cancer Center of Pelotas Santa Casa de Misericórdia , as well as to correlate such cancer with toxoplasmosis, through clinical and epidemiological data. A longitudinal cohort prospective study was carried out with a total of 95 patients, who were followed during the antineoplastic treatment by approximately two cycles, from March to November of 2010. The serological search was performed through Indirect Immunofluorescence Techniques (IFI) and Enzyme Linked Immunosorbent Assays (ELISA), and positive results to antibodies IgM anti-T. gondii were confirmed through Electrochemiluminescence Immunoassay (ECLIA). The epidemiological data were obtained through a questionnaire and the clinical, from the analysis of previously authorized patient dossiers. It was verified that the seropositive rate for IgG anti-T.gondii antibodies was of 84.21% at the pre-treatment chemotherapy sample, and of 83.33% at the post-treatment sample through the IFI technique, observing the low titration of antibodies, while through ELISA, 100% of the samples in both analysis were reagents. Class M antibodies were detected in six of the patients (6.3%) through IFI or ELISA and confirmed by ECLIA in one of them. In the risk factor analysis, it was noted a significant association (p<0.05) among seropositive patients for IgM in relation to the variables death (OR= 4.78) and race (OR= 10.88), respectfully. The results obtained point towards the necessity to perform the monitoring toxoplasmosis in cancer patients who are undergoing chemotherapy treatment, in order to avoid grave or even fatal consequences.